2012
DOI: 10.1080/13669877.2011.646288
|View full text |Cite
|
Sign up to set email alerts
|

The effects of label design characteristics on perceptions of genetically modified food

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae, and drug doses should be independently verified with primary sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The information already present on food label that is most requested and valued by consumers are: Designation of origin followed by the organic logo or country of origin (COO) label [78,85,113,118], the nutritional panel and warnings [113,118,139,150] (better if calculated per 100 g of product [75]), the expiry date or the date of the maximum shelf life [118,132] (with most preference for the wording "best before" [103]), and the price [112]. It is interesting to note that other information was reported as impactful for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…The information already present on food label that is most requested and valued by consumers are: Designation of origin followed by the organic logo or country of origin (COO) label [78,85,113,118], the nutritional panel and warnings [113,118,139,150] (better if calculated per 100 g of product [75]), the expiry date or the date of the maximum shelf life [118,132] (with most preference for the wording "best before" [103]), and the price [112]. It is interesting to note that other information was reported as impactful for consumers.…”
Section: Resultsmentioning
confidence: 99%
“…Although there has been research on the effects of source characteristics on warning effectiveness (Costello et al, 2002;Guttman & Peleg, 2003;Wogalter et al, 1999b), the intentions of manufacturers as the warning source have not received much attention in warning research. Though manufacturers have a responsibility to protect consumers from harm by law (Cox, 1999;Cox & Wogalter, 2006; Enforcement Rule of the Consumer Chemical Products and Biocides Safety Control Act, 2021), they have their own goals to maintain or increase their sales.…”
Section: Manufacturers' Interest and Strategies As The Warning Sourcementioning
confidence: 99%
“…Among these, van Kleef, van Trijp, and Luning (2005) and Verbeke, Scholderer, and Lähteenmäki (2009) tested the effect of FOP claims for functional foods, obtaining significant but different results depending on the type of claim and on the carrier products. Later, Hellier et al (2012) studied the effects of label colour, wording, content and information source on perceived hazard and WTB for GM food, finding significant differences among treatments. Recently, Vila-López and Küster-Boluda (2018) manipulated colour and health claims and confirmed that both kinds of attributes have a significant impact on young consumer attitudes and product trial.…”
Section: Product Specificitymentioning
confidence: 99%